The Role of Autobiographies in Activism: How Former 'Comfort Women' Used Testimonies to Fight for Their Rights - Bathgate, Kathryn (Satura, 2022)
Imagine you are in a room of women from different cultures and backgrounds. You may be inclined to think that these women have nothing in common. However, if you were to ask them if they had experienced sexual harassment, four of out five (81%) would raise their hands (Chatterjee). According to the National Sexual Violence Resource Center, one in five women have also been raped. Sexual violence defines the female experience. Female sexuality has always been centered around and dictated by men, their desires, and their sexual urges. Rebecca Solnit says, “sex is an arena of power” (108) and has long been a way to shame, control, and own women. Men have defined when, with whom, and under what circumstances women are allowed to have sex, and through an emphasis on female virginity, have controlled and regulated women and their bodies (Jung, Soh, and Solnit). Sex is one of the most basic components of human existence, and to exert control over someone’s sexuality is to take away their most basic freedom and their sense of security.